Food Process Engineering and Technology - Akash Pare; Mandhyan B.L (New Delhi New India, 2011)
This book containes information obtained from authentic and highly regarded sources.
Spores Viscosity Vacuum
Keywords: Spores, Viscosity, Vacuum